2020
DOI: 10.1002/jbm.b.34751
|View full text |Cite
|
Sign up to set email alerts
|

A high molecular weight hyaluronic acid biphasic dispersion as potential therapeutics for interstitial cystitis

Abstract: Interstitial cystitis (IC) is a progressive bladder disease characterized by increased urothelial permeability, inflammation of the bladder with abdominal pain. While there is no consensus on the etiology of the disease, it was believed that restoring the barrier between urinary solutes and (GAG) urothelium would interrupt the progression of this disease. Currently, several treatment options include intravesical delivery of hyaluronic acid (HA) and/or chondroitin sulfate solutions, through a catheter to restor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 63 publications
(68 reference statements)
0
11
0
Order By: Relevance
“…As normal human bladder urothelial cells are difficult to obtain for ethical reasons, while cell lines are widely accessible, our in vitro model consisted of the human non-invasive bladder cancer urothelial cell line RT4. In contrast to the more commonly used muscle-invasive bladder cancer urothelial cell line T24 in previously published in vitro IC/BPS models (18,20,21,23), RT4 cells isolated from grade I transitional cell carcinoma better reflect normal urothelial cells, especially with respect to differentiation markers (24, 25), as well as growth and migration characteristics (26). However, to increase the credibility of our results, we also confirmed our main findings from RT4 cells in normal porcine bladder urothelial (NPU) cells, which are more accessible and share most structural, molecular, and physiological features with normal human bladder urothelial cells (27-29).…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…As normal human bladder urothelial cells are difficult to obtain for ethical reasons, while cell lines are widely accessible, our in vitro model consisted of the human non-invasive bladder cancer urothelial cell line RT4. In contrast to the more commonly used muscle-invasive bladder cancer urothelial cell line T24 in previously published in vitro IC/BPS models (18,20,21,23), RT4 cells isolated from grade I transitional cell carcinoma better reflect normal urothelial cells, especially with respect to differentiation markers (24, 25), as well as growth and migration characteristics (26). However, to increase the credibility of our results, we also confirmed our main findings from RT4 cells in normal porcine bladder urothelial (NPU) cells, which are more accessible and share most structural, molecular, and physiological features with normal human bladder urothelial cells (27-29).…”
Section: Introductionmentioning
confidence: 95%
“…Furthermore, TNFa signaling pathway has been determined as significantly enriched in the bladders of IC/BPS patients, specifically in those with Hunner's lesions (17). It is therefore not surprising that published in vitro models of bladder urothelial cells frequently use TNFa to mimic an inflammatory milieu found in IC/BPS (18)(19)(20)(21)(22)(23). However, the exact effects of TNFa on global gene expression and alterations of cellular processes in urothelial cells are still not yet entirely known.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The biphasic system in the proportion of 1:1 does not increase the levels of IL-6, IL-8 or MCP-1 at concentrations of 1 and 3 mg/mL. In these conditions, the biphasic system decreases the permeability of the cell monolayer (assessed by the value of transepithelial electrical resistance (TEER)), making it a promising approach for IC treatment [169].…”
Section: Bladder Inflammationmentioning
confidence: 99%
“…In contrast, the follow-up study in 2020 revealed that none of the commercially available GAG formulations containing HA or HA with CS were able to attenuate the TNFα-induced production of IL8 and IL6, the expression of GAG synthesis enzymes, or markers of tissue remodeling and pain [ 34 ]. Later on, Rooney et al also reported on a newly developed biphasic system combining cross-linked and native HA in a 1:1 ratio that was able to reduce permeability, while at the same time did not alter the production of proinflammatory cytokines in HTB2 cells [ 35 ]. The significant recovery in various cystometric parameters following HA treatment was shown in vivo in H 2 O 2 -induced IC in female Wistar rats.…”
Section: Resultsmentioning
confidence: 99%